Design lessons on access features in PAPER - Theng, Yin-Leng (2009)
Using Nielsen’s Heuristic Evaluation, this paper reports a user study with six usability-trained subjects to evaluate PAPER’s access features in assisting users to retrieve information efficiently, part of an on-going design partnership with stakeholders and designers/developers. PAPER (Personalised Adaptive Pathways for Exam Resources) is an improved version evolving from an earlier implementation of GeogDL built upon G-Portal, a geospatial digital library infrastructure. After two initial evaluations with student and teacher design partners, PAPER has evolved containing a new bundle of personalized, interactive services with four modules : mock exam; personal coach (practice and review); trend analysis and performance review. This paper highlights lessons learnt in the design of PAPER using Nielsen’s heuristics, and discusses implications for the design of access features in digital libraries in general.